Proteomic response to 5,6-dimethylxanthenone 4-acetic acid (DMXAA, vadimezan) in human non-small cell lung cancer A549 cells determined by the stable-isotope labeling by amino acids in cell culture (SILAC) approach - Pan ST; Zhou ZW; He ZX; Zhang X; Yang T; Yang YX; Wang D; Qiu JX; Zhou SF (Dove Medical Press, 2015)
Shu-Ting Pan,1,* Zhi-Wei Zhou,2,3,* Zhi-Xu He,3 Xueji Zhang,4 Tianxin Yang,5 Yin-Xue Yang,6 Dong Wang,7 Jia-Xuan Qiu,1 Shu-Feng Zhou2 1Department of Oral and Maxillofacial Surgery, The First Affiliated Hospital of Nanchang University, Nanchang, Jiangxi, People’s Republic of China; 2Department of Pharmaceutical Sciences, College of Pharmacy, University of South Florida, Tampa, FL, USA; 3Guizhou Provincial Key Laboratory for Regenerative Medicine, Stem Cell and Tissue Engineering Research Center and Sino-US Joint Laboratory for Medical Sciences, Guiyang Medical University, Guiyang, 4Research Center for Bioengineering and Sensing Technology, University of Science and Technology Beijing, Beijing, People’s Republic of China; 5Department of Internal Medicine, University of Utah and Salt Lake Veterans Affairs Medical Center, Salt Lake City, UT, USA; 6Department of Colorectal Surgery, General Hospital of Ningxia Medical University, Yinchuan, 7Cancer Center, Daping Hospital and Research Institute of Surgery, Third Military Medical University, Chongqing, People’s Republic of China *These two authors contributed equally to this work Abstract: 5,6-Dimethylxanthenone 4-acetic acid (DMXAA), also known as ASA404 and vadimezan, is a potent tumor blood vessel-disrupting agent and cytokine inducer used alone or in combination with other cytotoxic agents for the treatment of non-small cell lung cancer (NSCLC) and other cancers. However, the latest Phase III clinical trial has shown frustrating outcomes in the treatment of NSCLC, since the therapeutic targets and underlying mechanism for the anticancer effect of DMXAA are not yet fully understood. This study aimed to examine the proteomic response to DMXAA and unveil the global molecular targets and possible mechanisms for the anticancer effect of DMXAA in NSCLC A549 cells using a stable-isotope labeling by amino acids in cell culture (SILAC) approach. The proteomic data showed that treatment with DMXAA modulated the expression of 588 protein molecules in A549 cells, with 281 protein molecules being up regulated and 306 protein molecules being downregulated. Ingenuity pathway analysis (IPA) identified 256 signaling pathways and 184 cellular functional proteins that were regulated by DMXAA in A549 cells. These targeted molecules and signaling pathways were mostly involved in cell proliferation and survival, redox homeostasis, sugar, amino acid and nucleic acid metabolism, cell migration, and invasion and programed cell death. Subsequently, the effects of DMXAA on cell cycle distribution, apoptosis, autophagy, and reactive oxygen species (ROS) generation were experimentally verified. Flow cytometric analysis showed that DMXAA significantly induced G1 phase arrest in A549 cells. Western blotting assays demonstrated that DMXAA induced apoptosis via a mitochondria-dependent pathway and promoted autophagy, as indicated by the increased level of cytosolic cytochrome c, activation of caspase 3, and enhanced expression of beclin 1 and microtubule-associated protein 1A/1B-light chain 3 (LC3-II) in A549 cells. Moreover, DMXAA significantly promoted intracellular ROS generation in A549 cells. Collectively, this SILAC study quantitatively evaluates the proteomic response to treatment with DMXAA that helps to globally identify the potential molecular targets and elucidate the underlying mechanism of DMXAA in the treatment of NSCLC. Keywords: DMXAA, non-small cell lung cancer, cell cycle, apoptosis, autophagy, SILAC